Heart rate variability in type 2 diabetes mellitus: A systematic review and meta-analysis. - Thomas Benichou; Bruno Pereira; Martial Mermillod; Igor Tauveron; Daniela Pfabigan; Salwan Maqdasy; Frédéric Dutheil (PLoS ONE)
Background Cardiac autonomic neuropathy in type 2 dibetes mellitus (T2DM) patients is frequent and associated with high cardiovascular mortality. Heart rate variability (HRV) is the gold standard to measure cardiac autonomic neuropathy. We aimed to conduct a systematic review and meta-analysis to evaluate the impact of T2DM on HRV parameters. Methods The PubMed, Cochrane Library, Embase and Science Direct databases were searched on 1st October 2017 using the keywords "diabetes" AND ("heart rate variability" OR "HRV"). Included articles had to report HRV parameters in T2DM patients and healthy controls measured during 24 hours with a Holter-electrocardiogram. Measurements of HRV retieved were: RR-intervals (or Normal to Normal intervals-NN), standard deviation of RR intervals (SDNN), percetange of adjacent NN intervals differing by more than 50 milliseconds (pNN50), square root of the mean squared difference of successive RR intervals (RMSSD), total power, Low Frequency (LF), High Frequency (HF) and LF/HF ratio, as per Task Force recommendations. Results We included twenty-five case-control studies with 2,932 patients: 1,356 with T2DM and 1,576 healthy controls. T2DM patients had significantly (P<0.01) lower RR-intervals (effect size = -0.61; 95%CI -1.21 to -0.01), lower SDNN (-0.65; -0.83 to -0.47), lower RMSSD (-0.92; -1.37 to -0.47), lower pNN50 (-0.46; -0.84 to -0.09), lower total power (-1.52; -2.13 to -0.91), lower LF (-1.08; -1.46 to -0.69]), and lower HF (-0.79; -1.09 to -0.50). LF/HF did not differ between groups. Levels of blood glucose and HbA1c were associated with several HRV parameters, as well as Time from diagnosis of T2DM. Conclusions T2DM was associated with an overall decrease in the HRV of T2DM patients. Both sympathetic and parasympathetic activity were decreased, which can be explained by the deleterious effects of altered glucose metabolism on HRV, leading to cardiac autonomic neuropathy.